2014
DOI: 10.1186/1471-2407-14-964
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib-induced severe toxicities in a Japanese patient with the ABCG2 421 AA genotype

Abstract: BackgroundSunitinib is a multi-targeted receptor tyrosine kinase inhibitor that acts against receptors for vascular endothelial growth factor and platelet-derived growth factor. Common toxicities of sunitinib treatment include hypertension, hand–foot syndrome, vomiting, and diarrhea, and the proportion of grade 3 or 4 adverse events relating to sunitinib treatment range from 1 to 13% for all categories. It is reported that increased exposure to sunitinib is associated with improved clinical outcomes but also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 18 publications
(20 reference statements)
0
22
0
1
Order By: Relevance
“…It was reported that this SNP was associated with an increase in systemic exposure to sunitinib, possibly causing thrombocytopenia and hypertension [23]. Miura et al [24] followed with a case report in 2014 describing a patient with mRCC who developed severe grade 3 and 4 adverse events on sunitinib, namely fever, thrombocytopenia, transaminase elevation, hypoxia, and pulmonary edema. Again, the AA genotype of rs2231142 in ABCG2 was suggested to explain these toxicities in Asians.…”
Section: Pharmacogenetics To Predict Sunitinib Toxicitymentioning
confidence: 99%
“…It was reported that this SNP was associated with an increase in systemic exposure to sunitinib, possibly causing thrombocytopenia and hypertension [23]. Miura et al [24] followed with a case report in 2014 describing a patient with mRCC who developed severe grade 3 and 4 adverse events on sunitinib, namely fever, thrombocytopenia, transaminase elevation, hypoxia, and pulmonary edema. Again, the AA genotype of rs2231142 in ABCG2 was suggested to explain these toxicities in Asians.…”
Section: Pharmacogenetics To Predict Sunitinib Toxicitymentioning
confidence: 99%
“…A study in people of Japanese descent reported a 1.9 - 3.5 times greater AUC of sulfasalazine in patients with the c.421C>A variant, but this finding was not replicated in a study of people of Chinese descent [83]. Other studies found that patients of Japanese descent with the c.421C>A variant who were being treated with sunitinib for advanced renal cell carcinoma were more likely to develop grade 3 or grade 4 thrombocytopenia [81,84,85], and that the variant was significantly associated with increased sunitinib exposure [86]. Furthermore, patients homozygous for the reference allele may have lower plasma concentrations of atorvastatin, simvastatin, and fluvastatin [1,87,88] and may respond more poorly to FOLFOX/XELOX therapy [89] compared to patients homozygous for the A allele.…”
Section: Abcg2 Variantsmentioning
confidence: 99%
“…Miura et al described a patient with metastatic RCC who exhibited grade 4 thrombocytopaenia and a 30% reduction in lesions after sunitinib treatment for 10 days 5. In that case, the blood concentration of sunitinib was much higher than usual.…”
Section: Discussionmentioning
confidence: 99%